Article RETRACTED due to manipulation by the authors Improving Soccer Coaching: Considerations of Individual Learning Styles, Intelligence Levels, and Motivation - Ahmad Chaeroni; Gusril Gusril; Kamal Talib; Mashuri Mashuri; Hendri Susilo; Bekir Erhan Orhan; Karuppasamy Govindasamy; Mottakin Ahmed; Ardo Okilanda (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Problem statement. In the increasingly complex and competitive world of soccer, training approaches that do not consider differences in individual learning styles, intelligence levels, and player motivation can be a serious obstacle in producing quality players. The lack of a holistic coaching approach based on differences in learning styles, intelligence levels, and motivation in training soccer players, which has the potential to hinder the development of optimal soccer playing skills among students, is a specific problem in this study. Purpose. The purpose of this study is to develop a holistic and innovative soccer coaching approach, which not only takes into account differences in individual learning styles and intelligence levels, but also increases player motivation. Thus, it is expected to be able to produce high-quality soccer players and improve the mastery of big ball games in physical education in schools. Methods. This type of research is a Quasy experiment with a study population of 140 men, the sample amounted to 44 male students. The instruments used were soccer playing skills test and general intelligence test. The data were analyzed using two-way analysis of variance with the help of Statistical Package for the Social Sciens 23. Results. The results of the study are as follows: (1) in general, the soccer playing skills of students who learn to use the global method are better than the elementary method; (2) there is an interaction between training methods and intelligence levels on the ability to play soccer; (3) at high intelligence levels, the global method is better than training using elementary learning methods to improve students' soccer playing skills; (4) at low intelligence levels, the elementary method is better than training using the global method in improving students' soccer playing skills. Conclusions. It can thus be concluded that improving soccer training cannot be underestimated without seriously considering individual learning styles, intelligence levels, and player motivation. Based on the findings, a holistic approach that integrates learning style preferences, designs training strategies that match intelligence levels, and understands motivational factors, opens the door to more adaptive and successful soccer learning.